A critical interrogation of the themes of politics and governance in the creative works of Mlalazi and Baya’s Crocodile of Zambezi (2008), Matsa and Baya’s Super Patriots and Morons (2003), and Chifunyise’s Waiting for the Constitution (2010) - Barure, Walter Kudzai (Midlands State University, 2014)
This study is an interpretive and descriptive analysis of the themes of politics and governance in contemporary Zimbabwe paying particular attention to the creative works of,Mlalazi and Baya’s TheCrocodile of Zambezi (2008) , Matsa and Baya’s Super Patriots and Morons (2003) and Chifunyise’s Waiting for the Constitution (2010). The study explores the power dynamics inherent in the insider/outsider, inclusion/exclusion, patriot/sell-out and self/nation schema and show how they are used to construct enduring critical, historical and political narratives in Zimbabwe. The theory underpinning the study is the postcolonial theory which was chosen because it overlaps from colonial politics into contemporary politics and governance.The study will also highlight how the ruling elite has resorted to repression, ideology, sovereignty and patriotic history as a way of maintaining and consolidating their power and constructing ‘desirable’ political identities. It will also capture the paradox of marginalization and empowerment which seem to coexist in the ideas of representation and resistance. This study concludes that the privileging of nationalist constructions of identity is also problematic because it renders invisible the multiplicity of identities which coexist within the same political space which is affected by globalization. Furthermore, identity is fluid and multi-layered rather than stable. Democracy is still an illusion and a fallacy in post-independent Zimbabwe because it is not founded on equality, economic and social justice